Pengaruh Dukungan Teman Dan Keluarga Terhadap Perilaku Pencegahan Penggunaan Napza Remaja - Ningsih, Febriyati Kusuma (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Drug abuse in Surabaya is one of the problems that is quite high. These problems often occur at the age of 10-19 years which is the age groups of student. Drug abuse prevalence in Surabaya city is 0,012%. Teenagers who use drugs abuse in 2013 were 29 students, it was 37 students in 2014 and increase up to 51 students in 2015. Factors that cause adolescents to use abuse drugs are family and friends.Â Family are factors that have great influence in the childâ€™s learning process. This is because children interact more with their family than with people at schoool. While for friends, interaction between oneself and peer is direct that occurs between individuals and individuals with groups. The contact involve children who have similar characteristics and at the same age level. The purpose of this research was to determina the effect of friend and family support on the behavior of drug use prevention of adolescents in Surabaya. This article is based on the results of research that conducted on junior high school students in Surabaya. The study used a quantitative approach method with observasional types. Sampling in this research use a total sampling technique that is as many as 77 adolescent respondents. Independent variables from this research are family and friend support. While the dependent variable is the behavior of drug use prevention. The results of this research are an influence between family support for drug use prevention (p= 0,031). While for friend support has an influence on the behavior of drug use prevention by (p=0,012). The conclusion in this research is that the characteristics of respondents are dominated by female gender. Respondents have a dominant age that is 13 years old. Research on respondents stated that both variables have an influence on drug use behavior for adolescents. Â